Understanding Alumni-Alma mater commitment relationships upstream and downstream - Pedro, Ilda Maria (2020)
This study collects reliable information about the commitment relationship (CR) between alumni and higher education institutions (HEIs) to increase the existing knowledge in terms of both theoretical and practical issues. Based on the literature review and findings from a previous qualitative research a theoretical model for a sample of 2008 alumni was tested through structural equation modeling. HEIs’ commitment, cognitive commitment, and affective commitment are drivers of CR, whereas the desire to share experiences, provide help, and participate in alumni meetings are the CR’s indicators. Findings offer insights to guide communication policies, focusing on overall quality, the key role of students in co-creation, strategies to involve students in campus life, the solicitation actions, and the advantages alumni can gain from their engagement. A contribution to the literature is also given because it reinforces the importance of strengthening aspects related to alumni-alma mater CR in contexts with a weak alumni culture.